O acesso à educação pelas crianças e adolescentes brasileiros com deficiência durante a pandemia da covid-19 - Vieira, Ingra Etchepare (2022)
Brazil is a signatory to the United Nations International Convention on the Rights of Persons with Disabilities, adopting the Doctrine of Integral Protection, as well as the principle of non-discrimination and the right of recognition. On the other hand, the reality faced by Brazilian childrens and adolescents with disabilities reveals difficulties, which were accentuated by the Covid-19 pandemic. Therefore the present work seeks the right to accessibility to promote the education of Brazilian children and adolescents with disabilities, during the Covid-19 pandemic, in a normative and doctrinal analysis based on bibliometrics carried out on the subject, wich is done with the purpose of protecting the following research problem: the extent to which the actors in charge of integral protection, especially society, including the scientific community, international agencies and Brazilian non- governmental organizations, and the Brazilian State, contributed, to the access to education of children and adolescents with disabilities in the period of the Covid-19 pandemic? The theoretical framework of the present work was composed by the works of the author Josiane Rose Petry Veronese and the theoretical contributions of the author Axel Honneth, from the book “The Struggle for Recognition: The Moral Grammar of Social Conflicts”. To answer the research problem, we opted for the deductive approach method and the monographic procedure method. The procedures used were the bibliographic and documental analysis, combined with the techniques of research of records; summaries; charts and bibliometric research of the legal scientific community on the subject, which was carried out on the Sucupira Platform website, more specifically in the “Qualis Periodicals” tool. With the analysis, it was found that the rights of children and adolescents with disabilities must be guaranteed with absolute priority by the agents responsible for their full protection, and their differences must be recognized and respected. Furthermore, the accessibility becomes essential for the promotion of the right to education of children and adolescents with disabilities, both rights being guaranteed in international laws and also at the domestic level. It was concluded that there is a scarcity of studies, published in the country´s highest quality journals, regarding the object of the present work, making the contributions of the scientific community, in these dissemination vehicles, unsatisfactory. With regard to the international agencies analyzed, it can be said that they contributed to the access to education of children and adolescents with disabilities, both in terms of the period when schools were closed and for the later period, with the resumption of classes, classroom or blended learning, as well as the non-governmental organizations studied and the Internet Management Committee in Brazil, with the exception of the National Council for the Rights of Children and Adolescents (CONANDA). However, the guidelines presented were not enough to promote concrete changes that guarantee access to education for students with disabilities during the Covid-19 pandemic, lacking articulation between the guidelines issued by international agencies and by the organizations of Brazilian society studied and public authorities.